Data Analytics Applications for Streaming Data From Social Media: What to Predict? - Emmert-Streib, Frank; Yli-Harja, Olli P.; Dehmer, Matthias (Frontiers in Big Data, 2018)
Social media in general provide great opportunities for mining massive amounts of text, image and video-based data. However, what questions can be addressed from analyzing such data? In this review we are focusing on microblogging services and discuss applications of streaming data from the scientific literature. We will focus on text-based approaches because they represent by far the largest cohort of studies and we present a taxonomy of studied problems.